Study on the Influence of Train Dynamic Load on underneath Tunnel Cast-in-Situ Concrete in Early Age - Yuchao Zheng; Baolin Liao; Fei Shen; Heng Zhong; Jianfeng Yang; Kai Liu; Lun Gong (Shock and Vibration)
The cast-in-situ concrete lining is prone to structural damage, cracks, and other defects, due to the influence of dynamic load at an early age, which is necessary to study the dynamic response. In this study, the finite difference software FLAC3D is used to carry out the dynamic analysis. Firstly, the reliability of the numerical model is verified by the train vibration test on-site. On this basis, the control variable method is used to analyze the dynamic response of the dynamic train load in early-age concrete structures under the factors of tunnel buried depth, train speed, cross angle, and surrounding rock grade. Then, the safety of the structure is evaluated. The numerical simulation results show that the influence of buried depth and surrounding rock on the early age structure is more obvious. Peak acceleration decreases with the increase in tunnel buried depth and increases with the increase in surrounding rock grade and train speed. Peak acceleration changes a little in the range of 0°–67.5°, but when the cross angle is 90°, the dynamic response reaches the minimum value. Multiple factors fitted the dynamic tensile stress, and the dynamic tensile stress under adverse conditions was calculated, compared with the splitting tensile strength of early-age concrete. The results show that the splitting tensile failure does not occur when the concrete age is more than 0.5 days.